Pemanfaatan Biji dan Tepung Sorgum Menjadi Produk Olahan Turunan Sorgum di Desa Tulabolo Barat, Kabupaten Bone Bolango - Widya Rahmawaty Saman; Sakinah Ahyani Dahlan; Karlena Arsyad; Zulham Sirajuddin; Silvana Apriliani; Rival Rahman (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
This community service project aimed to enhance the nutritional quality of processed food products by diversifying those made from sorghum. In Gorontalo, sorghum cultivation and processing into ready-to-eat food products were well-established. Active community participation in developing sorghum commodities was vital, prompting initiatives to process sorghum into widely recognized products. During training sessions, it was emphasized that all team members, from workers to management, needed to be knowledgeable and skilled in implementing Standard Sanitation Operational Procedures (SSOP) and Good Manufacturing Practices (GMP) to improve cleanliness and sanitation. The participants, primarily mothers from West Tulabolo Village, produced local food items from sorghum seeds, such as sorghum drinks, sorba, onde-onde, and fried bananas. While sorghum seeds were the main ingredient for sorghum drinks and sorba, sorghum flour was used for onde-onde and fried bananas. The program concluded with an evaluation of participants' acceptance of the products, showing high ratings of very much liked for nearly all aspects, including taste, texture, aroma, and color. This training was intended to guide the community in exploring entrepreneurial opportunities and fostering the development of village-based small and medium enterprises (UKM Desa).